Physicochemical and pasting properties of starch extracted from eleven sweetpotato varieties - Tsakama, M.; Mwangwela, A.M.; Manani, T.A.; Mahungu, N.M. (2010)
Physicochemical and pasting properties of starch extracted from eleven sweetpotato varieties wereevaluated. Relationships between starch properties were determined using correlation analysis.Significant differences were revealed among the physicochemical properties such as amylose, pH,granule size and size distribution. According to the Rapid visco analyzer (RVA) viscosity profiles, allstarches exhibited a type A profile which is characterized by high peak viscosity followed by majorbreakdown. However, significant differences were observed in individual pasting parameters such aspasting time, hot paste viscosity, cold paste viscosity, stability ratio, setback ratio and breakdown. Theresults revealed that variety has an effect on composition and pasting properties of sweetpotato starch.Correlations developed in this study were useful in predicting starch functionality when applied in foodindustry.